"Bullet colic" following renal gunshot wound. (July 2021) - Kaestner, L; Moore, A; Salukazana, S; Howlett, J; De Jager, S; De Wet, E; Lazarus, J
Selective non-operative management for penetrating injuries to the kidney is widely accepted. The management of a retained projectile within the kidney remains unclear. We present a case of bilateral renal gunshot wound (GSW) which was managed non-operatively. The patient presented with a peculiar complication of renal colic due to a migrated projectile 5 months post injury. Retained projectiles within the renal collecting system have a risk for stone formation and migration.